THE ROLE OF THE HEAD OF EDUCATION AS A CONTROLLER AND GUARANTEE OF EDUCATION QUALITY BASED ON INTEGRATED QUALITY MANAGEMENT - Kristina Anamaria Kewasi Uran; Hermania Bhoki; Yosep Belen Keban (STP Reinha Larantuka, 2024)
This thesis is entitled